FEATURES OF MOTIVATION OF EDUCATIONAL ACTIVITY OF STUDENTS – FUTURE PRACTICAL PSYCHOLOGISTS - Бондар, Л. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article presents a description of the motives of educational activity of students the third year direction of training "Practical Psychology". The personlity is a result of the educational process. The education and personal development is development, especially its needs and motives. Motives of educational activity affecte on the quality of training, the formation of the professional